Efektifitas Distraksi Visual dan Pernafasan Irama Lambat dalam Menurunkan Nyeri Akibat Injeksi Intra Kutan - Nikmatur Rohmah (Universitas Airlangga, 2007)
Introduction: The objective of this study is to examine the effectiveness of visual distraction usage and slow rhytm respiratory on pain relief which is caused by intra cutan injection.Methods: A quasy experimental design was used in this study. Sample of this study were 78 students of Nursing Academy Jember Muhammadiyah University at the second semester, recruited by using total sampling. Data were collected by using observation and questionnaire, then analyzed with Independent t-Test with significance level p<0.05.Results: The result showed that visual distraction and slow rhytm respiratory technique had significantly effect on the effort of decreasing pain (p= 0.000), and there was a correlation between visual distraction and slow rhytm respiratory technique had significantly effect with the effort of decreasing pain (p=0.019).Conclusion: slow rhytm respiratory technique was more effective than visual distraction technique to relief pain.